You don't fool me! Consumer perceptions of digital native advertising and banner advertising. Issue 4 (2nd October 2019) - Harms, Bianca; Bijmolt, Tammo H.A.; Hoekstra, Janny C.
ABSTRACT: This study investigates consumer perceptions of article-style native advertisements and banner advertisements, in terms of understanding the message intent, ad attitudes, and ad credibility. In addition, it examines the interrelationships of these constructs and their effects on the brand. Data retrieved from 303 respondents in an online experiment, analysed with partial least squares path modelling, show that, contrary to prior research, consumers actually evaluate banners more positively than article-style native ads, in terms of attitude and credibility. Banners also show a larger understanding of message intent. Ad attitude, ad credibility, and understanding of message intent significantly mediate the relations between ad type (banners versus article-style native ads) and brand effects. These results provide important insights for brand managers, ad agencies, and publishers that can increase the effectiveness of online advertising planning.